Annona cherimola Miller and Its Flavonoids, an Important Source of Products for the Treatment of Diabetes Mellitus: In Vivo and In Silico Evaluations - Fernando Calzada; Miguel Valdes; Jesús Martínez-Solís; Claudia Velázquez; Elizabeth Barbosa (MDPI AG, 2023)
The antihyperglycemic activity of ethanolic extract from Annona cherimola Miller (EEAch) and its products were evaluated using in vivo and in silico assays. An α-glucosidase inhibition was evaluated with oral sucrose tolerance tests (OSTT) and molecular docking studies using acarbose as the control. SGLT1 inhibition was evaluated with an oral glucose tolerance test (OGTT) and molecular docking studies using canagliflozin as the control. Among all products tested, EEAc, the aqueous residual fraction (AcRFr), rutin, and myricetin reduced the hyperglycemia in DM2 mice. During the carbohydrate tolerance tests, all the treatments reduced the postprandial peak such as the control drugs. In the molecular docking studies, rutin showed more affinity in inhibiting α-glucosidase enzymes and myricetin in inhibiting the SGLT1 cotransporter, showing ∆G values of −6.03 and −3.32 kcal/mol−1, respectively, in α-glucosidase enzymes. In the case of the SGLT1 cotransporter, molecular docking showed ∆G values of 22.82 and −7.89 in rutin and myricetin, respectively. This research sorts in vivo and in silico pharmacological studies regarding the use of A. cherimola leaves as a source for the development of new potential antidiabetic agents for T2D control, such as flavonoids rutin and myricetin.